Evaluasi Penerimaan Retribusi Parkir Di Tepi Jalan Umum Di Dinas Perhubungan (DISHUB) Kota Pekanbaru - SRI WAHYUNENGSIH; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract: Retribution is one of the main sources of finance reception areain the original income component. Department of Transportation (Affair)Pekanbaru City is one of the City Government which is responsible for managingone of the primal source of income is the one area on the edge of the parking levya public road by Regulation No. 14 of 2001 concerning the organization andmanagement of perpakiran. One effort to increase revenue Pekanbaru, PekanbaruCity Department of Transportation through levies, saw the potential of publiccurbside parking levy has great potential to contribute to the reception area. Thepurpose of this study: To evaluate the acceptance of curbside parking fees inpublic in the city of Pekanbaru Transportation Agency, and to determine thefactors that influence acceptance of curbside parking fees in public in Pekanbarucity Transportation Department.Data analysis method used in this research is descriptive qualitativeanalysis method that is based on trying to explain the phenomena that exist andexplore all the facts relating to the subject matter covered by the results ofresearch on the evaluation of Levy Proceeds In Public Road Parking InDepartment of Transportation (Transportation Agency) Pekanbaru.Based on the research and the analysis that has been conducted on thisstudy , obtained In the sub- indicators of the development of the second highestGDP Pekanbaru in Sumatra after Medan . Thus the possibility of receiving aroadside parking levy greater than that in the target of Rp . 5.5 Billion . Everincreasing population growth will certainly affect the increased revenue roadsideparking fees , due to the increase of population , the need Transporter toolincreasing two-wheeled one . In sub-indicators tariff adjustments , that there is adifference in the two-wheeler parking rates of legislation that has been establishedwith self-managed parking designated or established by the government , so it canbe assumed to be one cause of the reduced parking fees receipts in one curbsideparking rates difference . Factors affecting the acceptance of roadside parking feesin public by the city of Pekanbaru Pekanbaru Transportation Agency iscommunication , human resources , and disposition .Keywords: Evaluation, Acceptance, Parking Levy On Public Road